Emergency Department Thoracotomy: Too Little, Too Much, or Too Late. Issue 10 (October 2013) - Capote, Allan; Michael, Andrew; Almodovar, Jorge; Chan, Patricia; Skinner, Ruby; Martin, Maureen
Emergency department thoracotomy (EDT) is a dramatic lifesaving procedure demanding timely surgical intervention, technical expertise, and coordinated resuscitation efforts. Inappropriate use is costly and futile. All patients admitted to a Level II trauma center who underwent EDT from January 2003 to July 2012 were studied. The primary end point was appropriateness of EDT. Secondary end points were staff exposure, survival, and return to normal function. Eighty-seven patients including 59 patients with penetrating wounds had a mean loss of vital signs (LOV) 11.6 610.6 minutes and Injury Severity Score (ISS) of 45.8 ± 16.1, whereas 28 blunt injury patients had a mean LOVof 10.4 ± 11.5 minutes and ISS of 50.4 ± 19.4. Mortality was 81 per cent (48 of 59) in penetrating injury and 93 per cent (26 of 28) in blunt injury patients, respectively (odds ratio [OR] 2.99; P 0.21). Fifty-five EDTs were indicated with 10 survivors (18.2%) and 32 not indicated with three survivors (9.4%). Surgeons adhered to guidelines more compared with ED physicians (OR, 4.9; P = 0.03) whose patients were more likely to die (OR, 3.52; P = 0.124). Survivors (11 of 13 [84.6%]) were discharged home without significant long-term neurologic disability. EDT is lifesaving when performed for penetrating injury by experienced surgeons following established guidelines but futile in blunt injury or when performed by nonsurgeons regardless of mechanism.